2017
DOI: 10.1111/jpm.12367
|View full text |Cite
|
Sign up to set email alerts
|

Caring for an intimate stranger: parenting a child with psychosis

Abstract: Findings highlight the necessity to train mental health professionals to provide individualized information; facilitate family communication; address the parents' guilt, ambivalence, meaning attributions that compromise adjustment; and support them through the challenges of parenting a son or daughter with psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 40 publications
1
40
0
1
Order By: Relevance
“…Themes that were found in the qualitative studies suggested that illness perception was related to a redefinition of the parent-child relationship [40, 46]. A parental perception of the patient as being responsible for his/her illness was related to less parental differentiation between the patient and the illness [42] and to more negative parent-patient communication [47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Themes that were found in the qualitative studies suggested that illness perception was related to a redefinition of the parent-child relationship [40, 46]. A parental perception of the patient as being responsible for his/her illness was related to less parental differentiation between the patient and the illness [42] and to more negative parent-patient communication [47].…”
Section: Resultsmentioning
confidence: 99%
“…A mental illness, in comparison to a physical illness, was shown to be perceived by the parent as more devastating, unexpected, chronic, stigmatizing, and leading to the loss of the patient's organic personality [43]. It should be noted that parents' perceptions of their child's illness have been shown to change over time, ranging from their normalizing of the illness in the prodromal stage to seeing the illness as having an unpredictable outcome in the more chronic stages [40].…”
Section: Characteristics Of Illness Perception Among Parents Accordinmentioning
confidence: 99%
“…As shown in Fig. 1, 26 23 papers were selected: 12,16, 16 reported on the experiences of carers only, 12,16,[34][35][36][37][38][39][40][41][42][43][44][45][46][47] while seven reported on the experiences of patients, carers and other stakeholders. [27][28][29][30][31][32][33] Study characteristics are summarised in supplementary Table 1 including quality appraisal results that show that 20 of the 23 papers were rated as high-quality studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twelve papers reported on studies conducted in the UK (6 in England, 16,29,30,32,34,35 1 in Wales, 36 2 in Northern Ireland, 28,31 1 in Scotland, 12 and 2 not specified 37,38 ), with the remaining studies conducted elsewhere in Europe (Germany, 39,40 Greece, 41 Norway, [42][43][44] and the Republic of Ireland 33 ), Canada, 45 the USA 46 and Australia. 27,47 Although most studies reported on detention in general psychiatric hospitals, three papersall conducted in the UKreported on carers' experiences of assessment and treatment units and forensic services.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation